ASPEKTY WADLIWOŚCI CZYNNOŚCI PRAWNYCH SPÓŁKI KAPITAŁOWEJ - Kuniewicz, Zbigniew; Czepita, Stanisław (Wydział Prawa i Administracji UAM, 2002)
The authors discuss the legal implications of the lack of resolution by the AGM or board of directors to the completion of a legal transaction by a company, in accordance with the new Polish code of commercial partnerships and companies. The authors disagree with the common belief which says that because article 17 of the Polish code allows a company to take an appropriate resolution also after making a declaration, this provision assumes the construction of validation of absolute invalid legal act. By analysing some cases of purported validation of absolute invalid legal act in the Polish legal system, the authors show that such validation is in principle inadmissible in the Polish legal system. In the article it is claimed that the discussed situation is a case of an incomplete legal act (negotium claudicans), which takes no temporary legal effects until the moment when a resolution is taken or the appointed time runs out. The construction mentioned in article 17 of the Polish code of commercial partnerships and companies requires the consent of another body of the company rather than another person. 34
DEFECTIVENESS OF COMPANY’S LEGAL ACTIONS